Potential of Shariah Economy in Promoting Sustainable Economic Development in Indonesia - Haninah, Asytiya; Choiri, Miftakhul (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
Sharia economy is increasingly gaining attention as an alternative to a just and sustainable economic system. In the context of economic development, the sharia approach is not only oriented towards growth, but also pays attention to aspects of distribution, ethics, and social welfare. This article discusses the potential of sharia economy in driving sustainable economic development in Indonesia by highlighting the role of sharia financial institutions, zakat instruments, waqf, and microfinance. The methods used are literature studies and qualitative descriptive analysis. The results of the study indicate that sharia economy has an effective mechanism in reducing poverty, empowering communities, and creating an inclusive economic system. However, to maximize its contribution, strengthening regulations, increasing public literacy, and collaboration between the government, private sector, and religious institutions are needed